Effects of thermal stress on the photoinactivation and repair of photosystem II in two microphytobenthos communities - Bártolo, Cláudia Alexandra (2022)
The microphytobenthos (MPB), the communities of benthic microalgae that colonize the intertidal flats of estuaries, form highly productive and dense biofilms in the photic layer during diurnal low tides. MPB assemblages are exposed to extreme conditions such as high and low temperature, high irradiances and UV radiation, or high salinities. This study aimed to test the effect of extreme temperatures on the photoinactivation and repair of photosystem II (PSII) of these natural communities. The study was carried out in two intertidal sites of the Ria de Aveiro with different sediment characteristics and MPB communities, epipelic and epipsammic. Sampling was carried out during one year, from autumn 2020 to summer of 2021. Lincomycin was used to inhibit the repair of photoinactivation PSII. The study was also conducted in two species representatives of eppipelic and epipsammic communities, Seminavis robusta and Staurosirella guenter-grassii, respectively. The results showed an important effect of low temperature on PSII photoinactivation, for all sampling sites and occasions, and for both species. These results contradict a hypothesis recently put forward stating that abiotic stress, particularly low temperature, does not induce photoinactivation of PSII. It is concluded that more research is needed to clarify the true role of abiotic stress in PSII photoinactivation and algal productivity under natural conditions.